2003
DOI: 10.1103/physrevlett.91.075006
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Fusion-Evaporation and Direct-Interaction Nuclear Reactions using High-Intensity Laser-Plasma-Accelerated Ion Beams

Abstract: Heavy-ion induced nuclear reactions in materials exposed to energetic ions produced from high-intensity (approximately 5 x 10(19) W/cm(2)) laser-solid interactions have been experimentally investigated for the first time. Many of the radionuclides produced result from the creation of "compound nuclei" with the subsequent evaporation of proton, neutron, and alpha particles. Results are compared with previous measurements with monochromatic ion beams from a conventional accelerator. Measured nuclide yields are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The produced proton/ion beams accelerated by this mechanism (called Target Normal Sheath Acceleration -TNSA) exhibit advantageous characteristics, such as short pulse lengths, high currents and low transverse emittance, but they also show exponential energy spectra with almost 100% energy spread. So far, for proton beams the maximum energy that has been achieved is ∼60 MeV [3] and for ions (typically carbon and oxygen) ∼10 MeV/n [11]. The large energy spread and the relatively low maximum energy remain the significant impediments for this technique to be applied for medical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The produced proton/ion beams accelerated by this mechanism (called Target Normal Sheath Acceleration -TNSA) exhibit advantageous characteristics, such as short pulse lengths, high currents and low transverse emittance, but they also show exponential energy spectra with almost 100% energy spread. So far, for proton beams the maximum energy that has been achieved is ∼60 MeV [3] and for ions (typically carbon and oxygen) ∼10 MeV/n [11]. The large energy spread and the relatively low maximum energy remain the significant impediments for this technique to be applied for medical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Protons can also be accelerated from the front side of the target by charge separation-induced fields, but the energies are usually lower [9,32] and the beam quality is inferior to those of rear surface accelerated protons. Removing the hydrogen-containing contaminants from the target surfaces, for example, by heating of the target [34], leads to the acceleration of ions from the target material itself, such as carbon, fluorine, aluminum, lead, or iron [9,34,36,37]. The observed energies may reach 10 MeV per nucleon while the beam quality is similar to the proton beam.…”
Section: Solid Targets and Proton Accelerationmentioning
confidence: 95%
“…It has been shown that the ion energies can reach 10 MeV/nucleon, which results in 650 MeV energy for Fe-ions [9]. These ions can react with a secondary target: they may fuse and form highly excited compound nuclei, which evaporate neutrons, protons, and alpha-particles [9,37]. Depending on their initial excitation, that is, incident ion energy the reaction channel may be different, corresponding to a different cross section and product nucleus.…”
Section: Ion-induced Nuclear Reactionsmentioning
confidence: 97%
“…When an electrostatic shock is formed in a plasma with velocity v sh , incoming ions to the shock are reflected from the shock front with v ref ∼ 2v sh . The accelerated ions in this way have been expected to be used for various applications such as cancer therapy [10][11][12], isotope generation [13], and proton imaging [14].…”
Section: Introductionmentioning
confidence: 99%